Metabolic Changes In The Freshwater Fish Catla catla, Under Copper Cyanide Intoxication - Hosetti, B.B (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Laboratory evaluations were made to assess the metabolic changes in the carp, Catla catla exposed to sublethal concentrations of copper cyanide. Fish were exposed to two sublethal (0.253 and 0.152 mg/L) concentrations for a period of 15 days. At the end of the exposure period, levels of total protein, free amino acids (FAA), protease, glutamine, urea, ammonia, glycogen, lactate and pyruvate were assessed in different functional tissues (liver, muscle and gill). Results exhibited significant (p<0.05) dose dependent decline in total protein, glycogen, ammonia and pyruvate, while the FAA, protease, urea, and lactate levels exhibited significant increase in its activity in both the concentrations. There was a significant recovery observed in all the above biochemical parameters, in all the tissues of fish after the 7th d of the withdrawal of treatment. Significant alterations observed in the above parameters may be considered to be manifestation of stress induced by the toxicant and analysis of biochemical parameters in the fish tissue may serve as useful indices in environmental biomonitoring and surveillance.